(untitled) (CONFERENCE ON THE ROLE AND IMPORTANCE OF SCIENCE IN THE MODERN WORLD, 2025)
Radial immunodiffusion (RID) is a cornerstone serological technique for ensuring blood transfusion safety by quantifying critical plasma proteins, including immunoglobulins (IgG, IgM, IgA), complement components (C3, C4), and other transfusion-relevant antigens. This study comprehensively evaluates RID’s role in detecting immunological incompatibilities, such as irregular antibodies and complement deficiencies, to minimize transfusion-related risks, including hemolytic reactions, alloimmunization, and transfusion-related acute lung injury (TRALI). By analyzing RID’s sensitivity, specificity, cost-effectiveness, reproducibility, and applicability across diverse clinical settings, this research underscores its enduring relevance in transfusion medicine. Results from a large-scale analysis of 1,200 samples demonstrate that RID achieves high accuracy, affordability, and accessibility, making it particularly valuable in resource-limited environments. Despite its longer turnaround time compared to automated assays, RID’s simplicity and reliability position it as a vital tool for enhancing global transfusion safety.